Penggunaan Metode Active Learning Dalam Meningkatkan Antusiasme Belajar Mata Kuliah Microteaching Mahasiswa Universitas Sunan Giri Surabaya - Moch. Anieq Nafis; Muhammad Yusron Maulana El-Yunusi (CV. Satria Jaya, 2024)
Microteaching is included in the course of the Postgraduate Islamic Education Study Program at Universitas Sunan Giri Surabaya which is included in the East Java Pemprof scholarship students. One of the alternative solutions to the problem implemented by UNSURI's Islamic Education Postgraduate students is to carry out Islamic Religious Education learning by using learning methods that can increase student activity in learning, namely by using active learning methods. the research method used in this research is applied research method while collecting data by observation, interviews and documentation. The results of this study are: 1) Teaching practice activities carried out by Postgraduate PAI students at Sunan Giri University Surabaya that skills in teaching are very important, especially for students majoring in education who will later become a teacher. 2) The method used by the Postgraduate students of PAI Universitas Sunan Giri Surabaya focuses on the student centered approach and the method is based on active learning, which is centered on students and uses ways or steps that make students active in learning is a throwing puzzle. 3) This teaching practice is used as a provision to plunge into the real world of education.